Development of magnetorheological elastomer railway pads with a tunable stiffness/damping property for railway fastening systems - Cui, Shukun; Liu, Bingtong; Zhou, Yao; Liu, Changxi; Wang, Yazhou; Xiao, Junheng (Frontiers in Materials, 2023)
The railway pad plays an irreplaceable role in isolating the vibration and noise from rail/wheel interaction in railway components. A railway pad with variable stiffness and damping properties can adapt to various railway operating conditions for suppressing of railway noise and vibration. Unfortunately, to meet the practical requirements in railway fastening systems, which the railway pad should be able to bear heavy loads with low stiffness, both the material development and structural design need to be addressed for the application of magnetorheological elastomer (MRE). In this work, an MRE railway pad is designed, developed and experimentally tested. As illustrated by experimental results, the obtained MRE materials illustrate an obvious magnetorheological effect with the highest efficiency of 171% on storage modulus and 70% on loss factor. Coupling with the magnet controlling unit, the MRE railway pad is capable to control the stiffness and damping property under high loads. By adjusting the coil’s current from 0 A to 5 A, its static stiffness exhibits an enhancement from 37.9 kN/mm to 68.4 kN/mm, and the damping property increases from 8776.3 N•s/m to 10866.3 N•s/m. These results in this study are not only a successful demonstration of delivering a tunable stiffness and damping capability of the railway pad, but also pave the way for the development of MRE materials to achieve more rational applications.